Novel IL2RG Gene Mutation in One of Dizygotic Twins Causing Profound Changes of Receptor Structure - Rutkowska-Zapała, Magdalena; Szaflarska, Anna; Kluczewska, Anna; Ciȩciwa, Julia; Plewka, Jacek; Michalska, Anna; Siedlar, Maciej (Frontiers in Pediatrics, 2022)
Here we report a 4-month-old boy with a T-B+NK- Severe Combined Immunodeficiency (SCID) due to a novel mutation in exon 2 of the IL2RG, the gene encoding the interleukin common gamma chain (γc) of the cytokine receptors for IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21. Patient was derived from twin pregnancy. He presented recurrent infections of gastrointestinal tract, while his twin-brother was asymptomatic with no immune defects. In order to evaluate the effect of this unreported variant on the protein structure, a structural modelling process was performed showing prominent biochemical alterations of the protein features, including molecular weight, isoelectric charge, and possible changes to its secondary and tertiary structure.